2013
DOI: 10.12944/cwe.8.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Effect on The Biological Behavior of the Cucurbit Beetle Epilachna chrysomelina In Al- Qunfudah Province-saudi Arabia

Abstract: The spotted oriental cucumber beetle E.chrysomelina (F.) is an important pest which feeds on many vegetable crops. It attacks plants specially members of the family Cucurbitaceae like pumpkin, sweet gourd, bittergourd, cucumber, Cucumis mello, Cucurbita pepoand Citrullus lanatus (Talhoq, 1982). According to the Maps of Plant Pests of 1980 and 1990 the spread of E. chrysomelina was the scope of many of the cities of the world. The temperature is the main factor in the activity and behavior of many insects. It h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The damage to the leaves reduces the vegetative production of the host plant and consequently affects the plant growth and yield (Awadalla et al 2011). Aldigail et al (2013) in Saudi Arabia reported that E. chrysomelina as one of the phytophagous insects of cucurbit plants and is considered an economic pest. In addition, the severe damage of E. chrysomelina is capable of transmitting the squash mosaic virus (SQMV) (Cohen and Nitzany 1963;Campbell 1971 andLockhart et al 1982).…”
Section: Introductionmentioning
confidence: 99%
“…The damage to the leaves reduces the vegetative production of the host plant and consequently affects the plant growth and yield (Awadalla et al 2011). Aldigail et al (2013) in Saudi Arabia reported that E. chrysomelina as one of the phytophagous insects of cucurbit plants and is considered an economic pest. In addition, the severe damage of E. chrysomelina is capable of transmitting the squash mosaic virus (SQMV) (Cohen and Nitzany 1963;Campbell 1971 andLockhart et al 1982).…”
Section: Introductionmentioning
confidence: 99%